Changes in public service motivation: Can public administration education help cultivate it? - Huang, Wan-Ling (International review of administrative sciences, 2022)
This study aims to investigate the influence of public administration education on the development of college students' public service motivation over time. The data come from a four-wave panel survey of 868 Taiwanese undergraduate students who enrolled in college in 2015; 418 of them majored in public administration and 450 majored in business administration. Latent growth modeling was employed to capture a change of overall public service motivation and individual public service motivation dimensions. Our findings show that students' public service motivation tends to change during the college years, while public administration education may not significantly contribute to its development. Points for practitioners Research findings offer some implications for practice. Given that public service motivation seems to be changeable, it becomes relevant for public managers to invest in developing employees' motivation to serve and make a positive difference in others' lives. However, any in-service training aiming to foster employee public service motivation should not focus too much on knowledge delivery, but rather accentuate the establishment and practice of service values.